Religion, Culture, and Radicalism: Moderation Strategies in Multicultural Societies in An Era of Disruption - Fariduddin, Ecep Ishak; Hajar, Ibnu; Khomisah, Khomisah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research is driven by the urgent need to formulate religion- and culture-based moderation strategies as preventive and counter-radicalization efforts, particularly in light of the rising threat of intolerance and extremism in Indonesia. The primary aim of this study is to identify the contributing factors of radicalism in multicultural societies and to formulate effective and applicable moderation strategies within the framework of the disruptive era. This study employs a qualitative method using a moderative, religious, and cross-cultural approach, guided by Creswell’s framework. Data sources include scholarly literature, government policy documents (e.g., from Kemenag and BNPT), and digital religious-cultural content from social media and online platforms. Data collection was conducted through document analysis and digital observation using purposive sampling to ensure relevance to issues of radicalism and moderation in Indonesia. The data were analyzed thematically, following Creswell’s steps: organizing data, reading for general meaning, coding, developing themes, interpreting findings, and presenting results. The findings reveal that radicalism arises from weak religious literacy, cultural exclusivism, and social inequality, all of which are exacerbated by digital disinformation. Effective moderation strategies must include strengthening multicultural education, promoting interfaith dialogue, involving local religious and cultural leaders, and utilizing digital media for tolerance and inclusivity campaigns. Academically, this study holds strong urgency in enriching scientific discourse on religion and cross-cultural understanding and radicalism and in developing a contextual interdisciplinary approach for fostering a peaceful society amid the challenges of globalization.